REAKSI PASAR MODAL TERHADAP PENGUMUMAN PAKET KEBIJAKAN EKONOMI XVI (Studi Empiris Pada Saham Perusahaan Yang Masuk Dalam Indeks LQ 45) - Tirsa Rante; Syaikhul Falah; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to analyze whether there are significant differences in abnormal returns before and after the announcement of economic policy XVI and trading volume activity before and after the announcement of XVI economic policy on November 16, 2018. This study uses event study, where observations of the average abnormal return are carried out. and the average trading volume activityduring the 11 day observation period. In this study data was obtained from the Indonesia Stock Exchange. The data used in this study include daily closing stock prices (closing price), daily stock trading volume, and the number of shares outstanding. The sample used amounted to 45 LQ45 index companies. The results of this study indicate (1) there is no significant difference in abnormal returns before and after the announcement of economic policy XVI (2) on the trading volume activity indicator there are significant differences before and after the announcement of XVI economic policy.